Buckling isogeometric analysis of functionally graded plates under combined thermal and mechanical loads. (15th February 2017) - Yu, Tiantang; Yin, Shuohui; Bui, Tinh Quoc; Liu, Chen; Wattanasakulpong, Nuttawit
Highlights: Numerical results of thermal-buckling of FGPs under thermal-mechanical loads are presented. An effective and accurate IGA formulation using FSDT for FGPs is developed. Effects of gradient index, plate aspect ratio, skew angle, etc. on thermal-mechanical buckling are investigated. Stability diagrams of thermal-mechanical buckling of FGPs are presented. Abstract: Practical applications such as airplane wings are usually subjected to combined thermal and mechanical loads, and they hence are prone to buckling failure. Preceding works on the buckling of advanced materials, e.g., functionally graded materials, under combined thermal and mechanical loads are rather rare in literature. In this paper, we report new numerical results of thermal-mechanical buckling of functionally graded rectangular and skew plates (FGPs) under combined thermal and mechanical loads. The numerical responses of buckling are computed using isogeometric analysis (IGA) based on the first-order shear deformation plate theory (FSDT) without shear-locking effect. We present formulations and then provide validation of numerical results computed by the proposed formulation against reference existing solutions. Parametric study is also performed to explore insight into the effects of various numerical aspect ratios such as gradient index, plate aspect ratio, loading type, skew angle, and boundary condition, etc. on mechanical response of FGPs. The stability diagrams are also presented.